Dielectric properties of soils and assessment of their hydrothermal state under snow cover based on radio-echo sounding data - Yu. Ya. Macheret; A. V. Sosnovsky; A. F. Glazovsky (Лëд и снег)
Snow cover significantly affects the thermal regime of the underlying soils, and its assessment and monitoring are an urgent task of remote sensing studies. To solve it, data on their dielectric properties and their dependence on physical properties are necessary. Analysis of available data showed that the relative dielectric permittivity of soils most strongly depends on their moisture content and can vary from 2 to 40. This leads to a noticeable difference in the reflection coefficient from the interface between snow cover and dry and wet soils, which can be detected by radio-echo sounding. This opens up a new way to apply radar data to assess and monitor the hydrothermal state of soils under snow cover. Compilation of data on the typical reflectance properties of different soils in areas with permafrost and seasonal snow cover might be useful. The presence of wet snow cover on the surface of wet soils makes such systematic compilation more difficult.